Kajian Konsep Value for Money terhadap Pengukuran Kinerja Keuangan Rumah Sakit Umum Daerah Kota Tangerang Tahun 2022–2024 - Meriana Meriana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study is intended to analyze the implementation of the value for money approach in assessing financial performance at RSUD Kota Tangerang during the period of 2022–2024. The research employs a descriptive quantitative approach using secondary data derived from budget realization reports. This analysis carried out using three main ratios: economy, efficiency, and effectiveness. The findings show that the hospital’s financial performance is categorized as economical, as reflected by economy ratios under 100% throughout the observed year. In terms of effectiveness, performance was considered effective in 2022 and 2023 but declined in 2024, indicating that the revenue target was not fully achieved. Meanwhile, efficiency performance remains suboptimal, as efficiency ratios exceed 100%, suggesting that the costs incurred are higher than the revenue generated. Overall, the hospital demonstrates the ability to manage its budget economically and achieve revenue targets, but still faces challenges in improving resource efficiency. Therefore, efforts are needed to optimize cost management and enhance service productivity to achieve a balance among economy, efficiency, and effectiveness in line with the value for money principles.